STRATEGI PEMBELAJARAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning for students with special needs in inclusive elementary schools still faces challenges in implementing strategies that match diverse student characteristics. Inappropriate use of learning strategies can hinder the learning process and the achievement of inclusive education goals. This study aims to analyze in depth the implementation of learning strategies in inclusive education services for students with special needs at the elementary school level. This research employed a qualitative approach with a case study design. The research subjects consisted of four informants, namely classroom teachers, special education teachers, and shadow teachers. Data were collected through in-depth interviews, classroom observations, and documentation. The instruments used included interview guidelines, observation sheets, and learning documents. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that the implemented learning strategies are adaptive and differentiated according to students’ individual needs. Teachers combine collaborative, contextual, inquiry-based, and Project-Based Learning strategies by simplifying learning objectives and materials. The use of concrete, visual, and audio-visual media, along with the development of Individualized Education Programs (IEP), serves as a key strategy to enhance students’ understanding. Collaboration between classroom teachers and support teachers also strengthens the effectiveness of the learning process. In conclusion, the implementation of adaptive and individualized learning strategies contributes to more effective inclusive learning. This implies that teachers need to improve their competence in designing differentiated instruction in inclusive elementary schools.